2021
DOI: 10.1039/d1an00771h
|View full text |Cite
|
Sign up to set email alerts
|

A facile colorimetric aptasensor for low-cost chlorpyrifos detection utilizing gold nanoparticle aggregation induced by polyethyleneimine

Abstract: A colorimetric aptasensor for chlorpyrifos detection utilizing localized surface plasmon resonance (LSPR) of gold nanoparticles (AuNPs) aggregation coupling with a specific aptamer and cationic polyethyleneimine (PEI) has been developed. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…In 2021, another colorimetric aptasensor was derived by Soongsong et al for the detection of the very popular organophosphate (OP) pesticide chlorpyrifos. They employed the localized surface plasmon resonance (LSPR) technique and AuNP aggregates induced by a cationic polyethylenimine (PEI) and a particular aptamer . With the addition of chlorpyrifos, the aptamer was directly attached to it, releasing cationic PEI.…”
Section: Exploring Various Photochemical Processes For Pesticide Dete...mentioning
confidence: 99%
“…In 2021, another colorimetric aptasensor was derived by Soongsong et al for the detection of the very popular organophosphate (OP) pesticide chlorpyrifos. They employed the localized surface plasmon resonance (LSPR) technique and AuNP aggregates induced by a cationic polyethylenimine (PEI) and a particular aptamer . With the addition of chlorpyrifos, the aptamer was directly attached to it, releasing cationic PEI.…”
Section: Exploring Various Photochemical Processes For Pesticide Dete...mentioning
confidence: 99%
“…Indeed, colorimetry detection comes with changes in the optical properties of nanomaterials when they move from non-aggregated, monodispersed nanometric objects to clusters that aggregate and/or precipitate in solution, which usually show a red shift of their absorbance spectrum in the visible region [ 91 ]. As a typical study, Soongsong et al [ 92 ] reported on the realization of a facile colorimetric aptasensor to detect chlorpyrifos based on polyethyleneimine-induced aggregation of AuNPs ( Figure 12 ). In their work, the authors obtained citrate-capped AuNPs using heat-assisted chemical synthesis in wet conditions and tested their aggregation upon the addition of various amounts of polyethyleneimine that is known to displace the citrate ions coating the AuNPs surfaces leading to their aggregation because of the loss of electrical repulsion in solution.…”
Section: Biosensors Based On Hybrid Biomolecules-nanomaterials Compos...mentioning
confidence: 99%
“…Upon detection of chlorpyrifos, the aptamer-polyethyleneimine are broken and the free polyethyleneimine molecules adsorb onto the metal surface leading to aggregation and a color change from red to blue. Image adapted from [ 92 ] with permission of Royal Society of Chemistry, 2021.…”
Section: Figurementioning
confidence: 99%
“…The commonly used fluorescent aptasensor involves labeled aptamers, however, Xu et al demonstrated a self-fluorescence aptasensor, in which an Exo III-assisted catalytic hairpin assembly (EACHA) was used for chlorpyrifos detection. [37] In chlorpyrifos Electrochemical CuO NFs and c-SWCNTs 0.07 ng/mL [34] Electrochemical OMC-CS and Fc@MWCNTs-CS 0.33 ng/mL [35] Fluorescent QDs nanobeads and AuNPs 0.73 ng/mL [36] Fluorescent EACHA 0.93 ng/mL [37] Colorimetric AuNP and cationic PEI 7.4 ng/mL [38] acetamiprid Fluorometric cationic carbon dots (cCDs) 0.3 nM [41] Fluorescent β-cyclodextrin (β-CD)-carbon quantum dots (CDs) and RecJf exonuclease 3 nM [42] Fluorometric AuNPs and multiple complementary strands 2.8 nM [43] Electrochemical highly porous gold 0.34 nmol/L. [44]…”
Section: Chlorpyrifosmentioning
confidence: 99%
“…In their study, an DNA aptamer beacon fuel-8, the optimum beacon (K d = 90.511 � 21.424 nM), was used for chlorpyrifos detection and the LOD was 0.93 ng/mL. Colorimetric aptasensor was also developed for chlorpyrifos detection, [38] in which stable gold nanoparticle (AuNP) based localized surface plasmon resonance (LSPR) spectroscopy was powerful when coupled with a DNA aptamer of chlorpyrifos together with cationic polyethyleneimine (PEI). This colorimetric aptasensor showed linear response from 20 to 300 ng/mL and a detection limit at 7.4 ng/mL.…”
Section: Sersmentioning
confidence: 99%